Changes in Lactobacillus and Bifidobacterium Load in a Population of Iranian People with Papillary Thyroid Cancer: The Effect of Radioactive Iodine therapy - Sakineh Moghadam Shiri; Nahid Hashemi-Madani; Sara Cheraghi; Babak Fallahi; Sara Minaeian; Maryam Honardoost; Fereshteh Shahrabi; Mohammad E. Khamseh (Journal of Iranian Medical Council, 2026)
Background: To investigate the changes in Lactobacillus and Bifidobacterium load in a population of Iranian people with Papillary Thyroid Carcinoma (PTC) before and following Radioactive Iodine (RAI) therapy. Methods: This longitudinal cohort study included 28 healthy individuals and 30 PTC patients referred for RAI therapy. A total of 90 stool samples from the same 30 patients with PTC were collected one day before RAI therapy, two weeks and two months following RAI therapy. As a control group, 28 stool samples were collected from 28 healthy age-sex matched individuals. Stool microbiotas were detected using 16S rRNA gene sequencing. Results: Lactobacillus load was significantly lower in patients with PTC compared to the healthy individuals before (2.56 vs. 4.47 copies/gr stool, p=0.01) and two weeks after RAI therapy (3.51 vs. 4.47 copies/gr stool, p=0.02). Two months after RAI therapy, there was no significant difference in the load of Lactobacillus between the two groups (5.21 vs. 4.47 copies/gr stool, p=0.69). Moreover, the load of Lactobacillus increased significantly from 2.42 copies/gr stool before RAI therapy to 3.80 copies/gr stool at two weeks, and 5.27 copies/gr stool after two months of RAI therapy (p=0.01). On the other hand, there was no difference in the abundance of Bifidobacterium between the PTC and healthy individuals at different time points. Conclusion: This study indicated the difference in the load of Lactobacillus in PTC patients compared to healthy individuals. Moreover, it highlighted a significant increase in the load of Lactobacillus in PTC patients following RAI therapy. These results highlight the potential for microbiota modulations as an adjuvant therapy in PTC management